Exaggerated Response of Systolic Blood Pressure to Cycle Ergometer - Kim, Young Joo (Korean Academy of Rehabilitation Medicine, 2013)
OBJECTIVE: The aim of this study is to exam the effects of exercise modes on the systolic blood pressure and rate-pressure product during a gradually increasing exercise load from low to high intensity. METHODS: Fifteen apparently healthy men aged 19 to 23 performed the graded exercise tests on cycle ergometer (CE) and treadmill (TM). During the low-to-maximal exercises, oxygen uptake (VO(2)), heart rate (HR), systolic blood pressure (SBP) and rate-pressure product were measured. RESULTS: CE had a significantly lower maximum VO(2) than TM (CE vs. TM: 48.51±1.30 vs. 55.4±1.19 mL/kg/min; p<0.001). However, CE showed a higher maximum SBP (SBP(max)) at the all-out exercise load than TM (CE vs. TM: 170±2.4 vs. 154±1.7 mmHg; p<0.001). During the low-to-maximal intensity increment, the slope of the HR with VO(2) was the same as VO(2) increased in times of the graded exercise test of CE and TM (CE vs. TM: 2.542±0.100 vs. 2.506±0.087; p=0.26). The slope of increase on SBP accompanied by VO(2) increase was significantly higher in CE than in TM (CE vs. TM: 1.669±0.117 vs. 1.179±0.063; p<0.001). CONCLUSION: The SBP response is stronger in CE than in TM during the graded exercise test. Therefore, there is a possibility that CE could induce a greater burden on workloads to cardiovascular system in humans than TM.